ANALYZING FINANCIAL PERFORMANCE OF TURKISH DEPOSIT BANKS USING TOPSIS METHOD - Ova, Alper (My University, 2021)
Banking industry is indisputably the biggest part of the financial sector in Turkey. Regarding the importance of bankingindustry, this study aimed to investigate the financial performance of Turkish banking industry for the period between 2012and 2019 using TOPSIS method. For this purpose, firstly ten banks, which had the highest amount of assets, were ranked usingeight criteria since these banks represent a great percentage of the banking industry. Secondly, bank ownership types wereanalyzed and ranked. The results indicate that there is a decline in the performance of state owned banks. Foreign banksfounded in Turkey seemed to be the best performing bank type in the last three years. Moreover, in this set of ten banks, thebest bank from 2012 to 2017 was a state owned bank, the best bank in 2018 was a foreign bank founded in Turkey and thebest bank in 2019 was a privately owned bank.